A new species of Rotigonalia (Insecta: Hemiptera: Cicadellidae) from Peru with a key to males of the genus - Leal, Afonso Henrique; Mejdalani, Gabriel; Creão-Duarte, Antonio J. (Zootaxa, 2016)
Rotigonalia regina sp. nov. is described and illustrated based on a male specimen from Pasco, Peru. The holotype of R. regina is rather large in comparison with other specimens of the genus, but the inflated clypeus and the shape of the paraphyses support its inclusion in Rotigonalia Young, 1977. A key to males of the five known species of Rotigonalia is given.